The Analysis of Compliance with Internal Control Principles at Bank Syariah XXX Based on the COSO Integrated Framework 2013 - Khansa, Yarsita Salsabila Al; Violita, Evony Silvino (Jurnal Manajemen Bisnis, Akuntansi dan Keuangan, 2023)
This research aims to analyze the compliance with internal control principles at Bank Syariah XXX using the COSO Integrated Framework 2013. The research methodology is qualitative, involving documentation studies and interviews with relevant stakeholders in the bank. The analysis results indicate that Bank Syariah XXX has implemented the internal control principles proposed by the COSO Integrated Framework 2013. Supporting factors for this implementation include management commitment, a solid understanding of Sharia principles, and an integrated information system. This study provides valuable insights for Bank Syariah XXX to continually enhance the effectiveness of its internal controls in accordance with applicable standards.